1998
DOI: 10.1038/bjc.1998.94
|View full text |Cite
|
Sign up to set email alerts
|

Suppression by pravastatin, an inhibitor of p21ras isoprenylation, of hepatocarcinogenesis induced by N-nitrosomorpholine in Sprague-Dawley rats

Abstract: Summary The effect of pravastatin, an inhibitor of p21 ras isoprenylation, on hepatocarcinogenesis induced by N-nitrosomorpholine and on p2l s isoprenylation were investigated in male Sprague-Dawley rats. Rats received i.p. injections of pravastatin (10 and 20 mg kg-1 body weight) every other day and, from the beginning of the experiment, were given drinking water containing N-nitrosomorpholine for 8 weeks. Vesible white nodules and hepatic lesions staining positively for gamma-glutamyl transpeptidase or gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Several preclinical trials confirm an anticancer efficacy of statins, investigating the mechanisms leading to growth inhibition [36]. In a recent study, Sutter et al [22] showed that HMG-CoAR inhibitors decreased the proliferation of HCC cells by inducing apoptosis and cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Several preclinical trials confirm an anticancer efficacy of statins, investigating the mechanisms leading to growth inhibition [36]. In a recent study, Sutter et al [22] showed that HMG-CoAR inhibitors decreased the proliferation of HCC cells by inducing apoptosis and cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…In 1,2-dimethylhydrazine-induced colon car- cinogenesis in ICR mice, simvastatin and pravastatin significantly reduced tumor frequency (Narisawa et al 1994). Pravastatin has been shown to reduce the incidence and volume of N-nitrosomorpholine-induced rat hepatic neoplastic nodules (Tatsuta et al 1998) and NMU-induced rat colon carcinogenesis (Narisawa et al P. Kubatka et al 1996). Moreover, several studies in rodents have also shown preventive effects of lipophilic statins on the growth of diverse tumors (Hawk et al 1996;Inano et al 1997;Kikuchi et al 1997;Matar et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…High doses of lovastatin (500 mg/kg day), but not doses lower than 180 mg/kg day, induced an increased incidence of hepatocellular and pulmonary cancer in animal models (MacDonald et al, 1988); in rodents, fluvastatin was found to be associated with thyroid cancer and forestomach papillomas (Robison et al, 1994). On the other hand, in mice and rats, the chemically induced colon carcinogenicity was reduced by both simvastatin and pravastatin (Narisawa et al, 1994;Narisawa et al, 1996), and pravastatin also decreased the number and volume of N-nitrosomorpholine-induced hepatic neoplastic nodules (Tatsuta et al, 1998).…”
Section: B Statins and Cancer Risk Preventionmentioning
confidence: 99%